False positivity of FDG-PET/CT in a child with Hodgkin disease - ÖNEŞ, TUNÇ (WILEY, 2008)
Role of Positron Emission Tomography (PET) with F-18-2-fluoro-2-deoxy-D-glucose (FDG) in staging of Hodgkin disease is well established despite several controversies. We report a Stage III Hodgkin lymphoma patient with false positive FDG-PET/CT results. Seven-year-old male with Hodgkin lymphoma was in remission at end of chemotherapy. At third and fourth months of postchemotherapy follow-up, increased gallium uptake and positive FDG-PET/CT revealed lymphoid hyperplasia. He has been followed for 21 months without any evidence of disease. Despite its documented benefit, we believe that results of FDG-PET/CT should be interpreted with great caution in order to avoid unnecessary interventions.
Keywords: false positivity; FDG-PET/CT; Hodgkin; lymphoma; COMPUTED-TOMOGRAPHY; EMISSION-TOMOGRAPHY; LYMPHOMA; F-18-FDG; UTILITY